Chronic kidney disease among greenhouse workers and field workers in China. (September 2022) - Yan, Tenglong; Yang, Siwen; Zhou, Xingfan; Zhang, Chuyi; Zhu, Xiaojun; Ma, Wenjun; Tang, Shichuan; Li, Jue
Abstract: Background: Agricultural workers are at increased risk of developing chronic kidney disease of non-traditional etiology (CKDnt). The environment in solar greenhouse has high-intensity agricultural hazard factors. However, the association between solar greenhouse work and CKDnt remains unknown. Objectives: We aimed to evaluate the relationship among solar greenhouse work, field work, and CKDnt risk, and to explore gender differences in CKDnt risk among solar greenhouse workers. Methods: Solar greenhouse workers and field workers were selected as the greenhouse worker and field worker groups in a cross-sectional study. Individuals with an estimated glomerular filtration rate (eGFR) of <60 ml/min per 1.73 m 2 were defined as CKDnt patients. Binary logistic regression and generalized linear regression models were used to estimate the association among solar greenhouse workers, field workers and CKDnt. Furthermore, gender differences in CKDnt were also analyzed. Results: A total of 638 solar greenhouse workers and 231 field workers were included. The prevalence of CKDnt was 2.8% in the solar greenhouse workers and 0.4% in the field workers, and the prevalence of CKDnt was higher in female solar greenhouse workers than in males. The eGFR reduced by 20.0% (19.74 ml/min per 1.73 m 2 ) in the greenhouse worker group compared with that in the field worker group ( p  < 0.05). Generalized linear analysis showed that the level of eGFR was lower in women than that in men after adjusting for parameters ( β  = −10.99 [−12.79, −9.10]). Conclusion: Solar greenhouse workers may be at an increased risk of CKDnt, and women are more vulnerable. Graphical abstract: A hypothetical relationship between solar greenhouse working and chronic kidney disease of non-traditional (CKDnt) risk factors in solar greenhouse workers and field workers in China. Image 1 Highlights: Solar greenhouse workers are at an increased risk of CKDnt. Female solar greenhouse workers are more vulnerable to CKDnt. The prevalence and risk of CKDnt in solar greenhouse workers are significantly higher than those in field workers.